Flow-induced vibrations of two staggered cylinders with a moderate spacing and varying incident angles at subcritical Reynolds numbers. (15th August 2022) - Xu, Wanhai; Wu, Haokai; Song, Zhiyou; He, Ziqi; Wang, Enhao; Ge, Weifeng; Wang, Fanjun
Abstract: Two-degree-of-freedom (2DOF) flow-induced vibrations (FIV) of a stagger-arranged circular cylinder pair with a constant centre-to-centre spacing ratio  P / D = 6 . 0 and varying incident angles ( α ) are numerically studied. The two cylinders can oscillate freely in both the in-line and cross-flow directions. The Reynolds number range  R e = 1470 –10320 belongs to the subcritical flow regime. Two identical cylinders with mass ratios of  m ∗ = 2 . 6 and mass-damping parameters of  m ∗ + C a ζ = 0 . 013 are adopted in the present simulation. Four incident angles ranging from 0° to 90° with an increment of 30° are considered to investigate the effect of  α on the FIV responses, hydrodynamic characteristics and wake patterns of the two cylinders at this specific  P / D . For small incident angles (i.e.,   α = 0 ° and 30°), the influence of Cylinder II on the FIV of Cylinder I is almost negligible. In contrast, owing to the complicated wake–cylinder and wake–wake interactions, large-amplitude vibrations are found for Cylinder II at high reduced velocities ( V r ). The wake patterns suggest that the periodic vortex coupling arisen from the synchronous movements between the upstream vortices and Cylinder II contributes to maintaining a vibration mode that resembles wake-induced flutter (WIF). For large incident angles of  α = 60 ° and 90°, the two cylinders oscillate similarly and their response amplitudes experience decline at lower  V r values. The analyses of the wake characteristics demonstrate that the restrained wake widths and the stronger proximity interference between the two cylinders lead to the vibration attenuation. Highlights: FIV of two staggered cylinders with a moderate  P / D and varying  α at subcritical  R e is investigated. Important aspects of FIV are analysed for the stagger-arranged cylinder pair. WIF is observed for Cylinder II at small  α attributed to the periodic vortex coupling. Vortex coupling and enveloping are found in the far wake for large  α .